Fuzzy Logic Controllers and Applications (IntechOpen, 2025)
This book is divided into two sections: "Fuzzy Logic Controllers" and "Applications of Fuzzy Logic." It provides a comprehensive collection, with two chapters dedicated to fuzzy logic control theory and three chapters focusing on its practical applications. By merging foundational theory with real-world examples, the book offers both novice and experienced engineers a thorough understanding of how fuzzy logic can enhance system performance, particularly in cases where traditional methods struggle to model complex behaviors. Implementing fuzzy logic in control systems is an exciting and rapidly evolving field. This book aims to highlight its potential, inspiring further research and innovation. It encourages the next generation of engineers to harness the power of fuzzy logic in addressing the complex challenges of the future's technology-driven world.